Single Ended Primary Inductor Converter for Delta Conversion of PV Systems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electrical Energy can be generated by Photovoltaic (PV) systems. To achieve desired power range PV modules are connected both in series and parallel. There will be a difference between output power between PV cells, modules due to temporary shading, pollution or spread in cell behaviour.  PV output power will be reduced due to this. In this paper in order to get the same output power during such condition delta conversion concept is introduced with the help of a DC/DC SEPIC converter. This is a converter capable of averaging out the difference existing in output power between PV cells, modules existing in PV system. The converter is simulated in MATLAB software and the results obtained are compared with the prototype hardware results.